A quantum chemical computation insight into the donor-acceptor bond interaction of silver complexes with tetrylene - Sy, Tran Duc; Phuong Loan, Huynh Thi; Hiep, Dang Tan; Tat, Pham Van; Quang, Duong Tuan; Ai Nhung, Nguyen Thi (Vietnam Journal of Chemistry, 2017)
We computationally investigate the nature of chemical bonding from linear to bent structures of N-heterocyclic carbene-analogues of silver complexes (called tetrylene) AgCl-NHEMe (Ag-NHE) with E = C – Pb using quantum chemical calculations at the BP86 level with the various basis sets def2-SVP, def2-TZVPP, and TZ2P+. The geometry calculations find that the equilibrium structures of Ag-NHE system show major differences in the bonded orientation of NHPb ligand in Ag-NHPb compared with NHE ligands the slighter homologues Ag-NHE (E = C - Sn). The bond dissociation energy results show that the Ag-carbene bond in Ag-NHC is a strong bond and decreases from the slighter to the heavier homologues. The EDA-NOCV results indicate that the ligand NHE in complexes is strong s-donors and very weak π donor. The NOCV pairs of the bonding show small π-back donation from the Ag to the NHEMe ligands. Keywords. N-heterocyclic tetrylene, bond dissociation energy, quantum chemical calculations, bonding analysis.